At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Answer: Choice A
f(1) = 2
f(n) = 2*f(n-1) for n ≥ 2
===========================================================
Explanation:
n = term number
So for instance, n = 3 represents the index for the 3rd term
We see that when n = 1, f(n) = 2 as shown by the left-most red point.
This means that f(1) = 2 which is a short way of saying "the first term is 2".
So the answer is between A and C.
Let's randomly guess that it might be choice C. We'll use the recursive rule given to generate the next term
f(n) = 4*f(n-1)
f(2) = 4*f(2-1) .... replace every n with 2
f(2) = 4*f(1)
f(2) = 4*2 ..... replace f(1) with 2, since f(1) = 2
f(2) = 8
This tells us that the 2nd term is 8, but the graph says it should be 4. Note the red point at (2,4)
Ultimately this all means that we can eliminate choice C and go with choice A as the final answer.
As a check, let's plug n = 2 into the recursive rule for choice A
f(n) = 2*f(n-1)
f(2) = 2*f(2-1)
f(2) = 2*f(1)
f(2) = 2*2
f(2) = 4
We get the proper second term. I'll let you check the other remaining terms. The notation 2*f(n-1) means "multiply 2 by the previous (n-1) term". In other words, the term values are doubling {2,4,8,16,...}
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.